MUSCULAR SYSTEM OF EUCONODONT ANIMALS AND THEIR SYSTEMATIC POSITION (EUCONODONTOPHYLEA) - Kasatkina A.P. (My University, 2006)
The muscular system of euconodont animals was studied in detail on the basis of the photographs of imprints from the Lower Carboniferous Shrimp Bed of Granton (Scotland), Upper Ordovician Soom Shale (South Africa), and Silurian Waukesha biota (North America). Superficial body structures are for the first time recognized for euconodont animals: external rings (annulation) (Panderodus imprint) and their traces (specimens 2 and 3 from Granton). This makes them looking like many invertebrates, such as annelids, priapulids, or pentastomids, and different from primitive chordates. In all other imprints of euconodont animals, a deep frontal break reaching their central part uncovers the inner transversal structures of the body, muscular fibers. As in invertebrates, they have different orientation. The medial apices of the fibers can be directed obliquely towards either the head (specimens 1, 2, 4, 5, 7 from Granton, and Promissum pulchrum Kovacs-Endrхdy imprints) or the tail (specimens 2 and 6 from Granton) or to be perpendicular to the body axis (specimens 3-5 from Granton). Discontinuity of the transversal structures (specimens 1 and 6) appears to occur in the euconodont animals. This suggests that the transversal obliquely-oriented structures visible on the euconodont imprints, are not myomers typical of chordate animals. Differently directed position of medial apices of the obliquely- oriented muscular fibers depends, probably, on physical state (direction of movement) of the animal. The longitudinal median structure, in our opinion, cannot be considered a chord, but is rather a gut extending from pharynx to anus. Apparently, in spite of visual similarity, the euconodont animals under study cannot be classified as chordates, or chaetognaths, or pentastomids. Their muscular system differs from that of all known groups of animals and shows its own unique structure: its inner transversal structures are muscular fibers, which externally look like rings (annulation). This supports our earlier conclusion (Kasatkina & Buryi, 1997) that euconodonts constitute a separate phylum, Euconodontophylea Kasatkina & Buryi, 1997.
Keywords: EUCONODONTOPHYLEA; EUCONODONT ANIMALS; MUSCULAR SYSTEM; SYSTEMATIC POSITION